Peran Executive Function (Fungsi Eksekutif) terhadap Kesiapan Sekolah: Pemahaman Guru PAUD - Muchammad Arif Muchlisin; Ika Juhriati; Dwiyani Anggraeni; Rini Meiwaty; Rini Arbaniyah (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2023)
Previous research discussed teachers' understanding of the role of the executive function in learning mathematics, reading, arithmetic, and those with neurological disorders. The focus of this research is to explore teachers' understanding of the role of the executive function on school readiness. A quantitative approach is applied in this study with a survey model. A total of 95 teachers of Early Childhood Education (PAUD) in Bekasi and Klaten Regencies participated in filling out the questionnaire. Data was collected using a questionnaire instrument by considering several literatures. Research data analysis was assisted by the SPSS version 25 program to present data descriptively, then analyzed by One-Way ANOVA, Two-Way ANOVA and independent sample t tests. The first finding indicates that PAUD teachers consider the role of the executive function for school readiness to be quite important. Then, this understanding is not related to the teacher's years of teaching experience. In addition, teachers who know about executive functions differ significantly from teachers who do not know about executive functions. The implications of these findings are discussed. ABSTRAK Penelitian sebelumnya membahas tentang pemahaman guru terhadap peran fungsi eksekutif terhadap pembelajaran matematika, membaca, aritmatika, dan dengan gangguan neurologis. Fokus penelitian ini adalah untuk mengeksplorasi pemahaman guru tentang peran fungsi eksekutif terhadap kesiapan sekolah. Pendekatan kuantitatif diterapkan dalam studi ini dengan model survei. Sebanyak 95 guru Pendidikan Anak Usia Dini (PAUD) di Kabupaten Bekasi dan Klaten berpartisipasi untuk mengisi kuesioner. Data dikumpulkan menggunakan instrumen kuesioner dengan mempertimbangkan beberapa literatur. Analisis data penelitian dibantu dengan program SPSS versi 25 untuk menyajikan data secara deskriptif, kemudian dianalisis dengan uji One-Way ANOVA, Two-Way ANOVA dan independent sample t test. Temuan pertama mengindikasikan bahwa Guru PAUD menganggap peran fungsi eksekutif untuk kesiapan sekolah tergolong cukup penting. Kemudian, pemahaman ini tidak berhubungan dengan tahun pengalaman mengajar guru. Selain itu, guru yang mengetahui tentang fungsi eksekutif jauh berbeda secara signifikan dibandingkan dengan guru yang tidak tahu tentang fungsi eksekuitf. Implikasi dari temuan ini dibahas.